2014
DOI: 10.1108/ijwhm-08-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and incivility: a systematic review of interventions

Abstract: Purpose -Workplace mistreatment has a negative impact on the health and well-being of approximately 20 per cent of workers. Despite this, few interventions have been evaluated and published. The purpose of this paper is to address the question "what interventions designed to reduce workplace bullying or incivility are effective and what can be learnt from evaluated interventions for future practice?" Design/methodology/approach -A systematic review was undertaken in which 11 electronic databases were searched,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
145
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 55 publications
3
145
1
2
Order By: Relevance
“…Related research on workplace bullying has so far focused on the interventions against and preventions of workplace bullying, and their success has been measured by evaluating the reduction in prevalence rates (Escartin, 2016;Hodgins, 2014). Recommendations have often been based on research findings regarding the antecedents and correlates of workplace bullying (Hodgins et al, 2014;Saam, 2010;Salin, 2009). However, only few studies have addressed the effects of such measures on workplace bullying (Hodgins et al, 2014;Saam, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Related research on workplace bullying has so far focused on the interventions against and preventions of workplace bullying, and their success has been measured by evaluating the reduction in prevalence rates (Escartin, 2016;Hodgins, 2014). Recommendations have often been based on research findings regarding the antecedents and correlates of workplace bullying (Hodgins et al, 2014;Saam, 2010;Salin, 2009). However, only few studies have addressed the effects of such measures on workplace bullying (Hodgins et al, 2014;Saam, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations have often been based on research findings regarding the antecedents and correlates of workplace bullying (Hodgins et al, 2014;Saam, 2010;Salin, 2009). However, only few studies have addressed the effects of such measures on workplace bullying (Hodgins et al, 2014;Saam, 2010). This study showed that the elements of the formal and informal systems inherent in the ethical infrastructure against workplace bullying are interrelated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the findings from Einarsen and Nielsen, 2015;Hodgins, et al, 2014;and Rousseau, et al, 2014, show that targets of workplace bullying are not just bullied four or five times, as the rats in the Miczek study, they often face months or even years of abuse (Hollis, 2016). During such abuse, the stress hormone is consistently poured into the brain, killing brain neurons.…”
Section: Brain Damage and Bullyingmentioning
confidence: 99%